(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Yoni Srava is an annoying symptom that usually reflects infective conditions of genital tract in females. One of the Yonivyapada having Yonisrava as its prominent symptom is Kaphaja Yonivyapada which can be co-related to Trichomoniasis or Candidiasis infections. In Kaphaja Yonivyapada, symptoms of itching along with sticky and unctuous discharges per vaginum have been illustrated. The patient may experience either mild and dull pain or no pain at all. In severe Trichomonas infection, there is mild to moderate pain at the genital organs due to inflammatory changes, though in most cases, it may be painless. Considering all the symptoms, mentioned by Acharya Charaka and others, the Kaphaja Yonivyapada can be closely compared with Trichomonas Vaginitis. A 46 years old female patient was presented with the complaints of itching in vulvar region and white discharge per vaginum since 3 months. On clinical evaluation, ulceration was present on bilateral labia minora along with strawberry spots on vaginal walls, yellowish-white discharge and cervical congestion. Aim and Objective: To study the efficacy of Sthanik Chikitsa along with oral Ayurvedic formulations in Kaphaja Yonivyapada (Trichomoniasis). Nimbadi Kshaya Yoni Dhavan followed by Mahanimba Taila Pichu twice a day for seven days along with oral herbal formulation is prescribed to the patient. Results: After completion of the treatment protocol patient got relief in her symptoms like itching in vulvar region and white discharge per vaginum. Conclusion: In Kaphaja Yonivyapada, especially Trichomonas Vaginitis Ayurvedic management by the use of Mahanimba (Melia azedarach) containing formulations for Sthanik Chikitsa are quite effective as Mahanimba is having Krimighna and Kandughna properties.